Nature’s Poetry Unveiled: Exploring the Symbolism and Design Philosophy of Chinese and Persian Gardens through Metaphor and Art - Li, Mengbi; Chau, Hing-Wah; Jamei, Elmira; Pourakbar, Hamidreza (Landscape Architecture and Art, 2023)
This paper delves into the symbolism and design philosophy of Chinese and Persian gardens, revealing the profound depths of their metaphorical and artistic expressions. As landscape architecture, gardens act as conduits for cultural transmission, embodying an understanding of the cosmic order and reflecting the passage of history. Focusing on pre-modern Chinese and Persian gardens, this study explores their design philosophy and characteristics. Chinese gardens prioritise the harmonious coexistence of humanity and nature, exemplified through a deep reverence for the natural world. Meticulous treatment of the landscape seamlessly integrates gardens with their surroundings, drawing inspiration from elements found in Chinese landscape painting. Persian gardens, on the other hand, showcase the distinctive Chahar Bagh layout, providing glimpses into an ideal cosmic order. Influenced by the beauty of Persian poetry, these gardens take on the essence of living poems, evoking a sense of tranquillity and allegorical meaning. Waterways, pavilions, and lush vegetation create captivating oases within the arid landscape, inviting relaxation. By analysing the architecture, symbolism, and design philosophy of both Chinese and Persian gardens, this study uncovers the remarkable similarities and differences that exist between them. However, these gardens extend beyond their physical manifestations, beckoning visitors to engage with metaphorical realms. The integration of poetry, painting, and various art forms enriches the multidimensional experience, eliciting profound sentiments and unlocking the transformative power of nature’s poetry. Ultimately, Chinese and Persian gardens embody the very essence of nature’s poetry, serving as bridges between built environments, humanity, and the natural world. Through the harmonious fusion of art, design, and the intricate relationship between humans and nature, these gardens inspire awe and reveal the timeless beauty that resides within nature’s realms.